Effects of a singular dose of mangiferin-quercetin supplementation on basketball performance: A double-blind crossover study of high-level male players - Bourdas, D. I.; Travlos, A. K.; Souglis, A.; Stavropoulou, G.; Zacharakis, E.; Gofas, D. C.; Bakirtzoglou, P. (Nutrients, 2024)
Pre-exercise mangiferin-quercetin may enhance athletic performance. This study investigated the effect of mangiferin-quercetin supplementation on high-level male basketball players during a basketball exercise simulation test (BEST) comprising 24 circuits of 30 s activities with various movement distances. The participants were divided into two groups (EXP = 19 and CON = 19) and given a placebo one hour before the BEST (PRE-condition). The following week, the EXP group received mangiferin-quercetin (84 mg/140 mg), while the CON group received a placebo (POST-condition) before the BEST in a double-blind, cross-over design. The mean heart rate (HR) and circuit and sprint times (CT and ST) during the BEST were measured, along with the capillary blood lactate levels (La-), the subjective rating of muscle soreness (RPMS), and the perceived exertion (RPE) during a resting state prior to and following the BEST. The results showed significant interactions for the mean CT (p = 0.013) and RPE (p = 0.004); a marginal interaction for La- (p = 0.054); and non-significant interactions for the mean HR, mean ST, and RPMS. Moreover, the EXP group had significantly lower values in the POST condition for the mean CT (18.17 ± 2.08 s) and RPE (12.42 ± 1.02) compared to the PRE condition (20.33 ± 1.96 s and 13.47 ± 1.22, respectively) and the POST condition of the CON group (20.31 ± 2.10 s and 13.32 ± 1.16, respectively) (p < 0.05). These findings highlight the potential of pre-game mangiferin-quercetin supplementation to enhance intermittent high-intensity efforts in sports such as basketball.